Preparing students for interprofessional collaboration in services for children with special needs in Finland: A document analysis - Kallio Hanna; Salminen Jaanet; Tuominen Miia (Sage Journals, 2023)
Introduction
Multiple types of support and expertise are needed for the benefit of children with special needs, with the collaboration between psychologists, social workers and special education teachers playing a key role. Here, we studied the extent of their academic training in interprofessional collaboration.
Methods
A document analysis of 24 curricula with 1699 courses from eight Finnish universities was applied. The courses focused on interprofessional collaboration were selected for the analysis. The course information was analysed with descriptive statistical methods, content analysis and qualitative quantification.
Results
A total of 38 courses focused on interprofessional collaboration. The courses were often mandatory; however, in psychology, they were often optional. The content of the courses included the basis of interprofessional collaboration, collaboration skills, and service systems and network familiarity. Two courses were common for the social work, psychology and special education programmes. Various learning methods were used, with five courses being based on independent online self-study.
Discussion
Considering the need for studies focusing on interprofessional collaboration, it was contradictory that these were largely maintained within one discipline and some were realised as independent self-studies. The variability of the curricula may reflect on students’ professional skills. For the collaboration of professionals working with children with special needs, it is also needed to deepen familiarity with cross-sectional services and the school system.